Badan Usaha Milik Desa: Strategi Penguatan Status Hukum untuk Pemberdayaan Masyarakat di Desa Batetangnga - Aminuddin, Aminuddin (Sekolah Tinggi Agama Islam Negeri Majene, 2024)
Although Village-Owned Enterprises (BUMDes) play an important role as drivers of the local economy, the regulations governing their legal status remain unclear, as shown in Government Regulation No. 43/2014 and Ministry of Village Regulation No. 4 of 2015. This uncertainty has led to public doubts about the legitimacy and accountability of BUMDes, thereby reducing public trust. This research focuses on the ambiguity of the legal status of Village-Owned Enterprises (BUMDes) in Batetangnga Village and its impact on management transparency and accountability. A qualitative research approach is used to explore the views and perceptions of the Batetangnga Village community and BUMDes managers regarding the legal status and management of BUMDes. Data were collected through interviews and participatory observation, then analyzed using thematic analysis techniques. The results indicate that weaknesses in the legal status of BUMDes lead to ambiguity in the roles and responsibilities of managers and hinder transparency, especially in financial aspects of Batetangnga BUMDes. This aligns with Institutional Theory, which states that legal uncertainty reduces incentives for agents (managers) to report activities transparently to the owners (village community). Furthermore, this research finds that weaknesses in legal status hinder BUMDes's ability to establish partnerships with external parties and limit flexibility in managing village assets, impacting Village Original Revenue (PADesa). This study recommends strengthening the legal status of BUMDes to enhance transparency, accountability, and public trust. Thus, BUMDes can optimally fulfill its role as an economic driver that contributes to the welfare of village communities.